Associations Between Aerobic Fitness and Cognitive Control in Adolescents - Westfall, Daniel R.; Gejl, Anne K.; Tarp, Jakob; Wedderkopp, Niels; Kramer, Arthur F.; Hillman, Charles H.; Bugge, Anna (Frontiers in Psychology, 2018)
Previous research has found positive associations between cognitive control and aerobic fitness in preadolescents and adults; however, fewer studies have investigated these associations in adolescents. Adolescence is of particular interest due to continued maturation of the prefrontal cortex; an area that subserves cognitive control. This study investigated the associations of aerobic fitness and cognitive control in adolescents. An assessment of aerobic fitness (Andersen intermittent running test) and two tests of cognitive control were collected to investigate these associations. Participants completed a test of inhibitory control (flanker task) and a test of cognitive flexibility (switch task). Along with traditional measures of reaction time (RT) and accuracy, diffusion modelling was utilized to combine these measures to calculate latent variables (i.e., drift rate, boundary separation, and nondecision time). Associations between cognitive measures and fitness were assessed with linear regressions while controlling for potential confounding factors. Higher fitness was associated with shorter reaction time and higher accuracy in the flanker task, indicating better inhibitory control performance. In addition, greater aerobic fitness was associated with greater quality of information uptake in the flanker task, as indicated by drift rate. In the switch task, higher aerobic fitness was associated with greater accuracy and longer switch RT indicating a speed-accuracy tradeoff. Results from the switch task diffusion modelling supported this conclusion as indicated by greater fitness associated with greater boundary separation, or response conservativeness. Further, greater drift rate in the switch task was associated with greater fitness. These findings corroborate growing evidence indicating the importance of aerobic fitness for inhibitory control and cognitive flexibility. This study extends the literature by demonstrating these effects in a large sample of adolescents with a computational model of the mechanisms that underlie cognition.